The Popularity Function: A Spurious Regression? The Case of Austria - Reinhard Neck; Friedrich Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper we apply the unit root and cointegration methodology of modern econometric time series analysis to estimated popularity functions for the Austrian parties in government since the mid-1970s. We find no evidence for and rather strong evidence against influences of unemployment or inflation on the popularity of the political parties in the federal government, thereby challenging previous studies that claimed to have established such influences. The usefulness of the applied methodology to clarify such questions is demonstrated by this example.
Keywords: D72; C22; D78; 330